If it's not what You are looking for type in the equation solver your own equation and let us solve it.
23=44-(-n)
We move all terms to the left:
23-(44-(-n))=0
We add all the numbers together, and all the variables
-(44-(-1n))+23=0
We calculate terms in parentheses: -(44-(-1n)), so:We get rid of parentheses
44-(-1n)
determiningTheFunctionDomain -(-1n)+44
We get rid of parentheses
1n+44
We add all the numbers together, and all the variables
n+44
Back to the equation:
-(n+44)
-n-44+23=0
We add all the numbers together, and all the variables
-1n-21=0
We move all terms containing n to the left, all other terms to the right
-n=21
n=21/-1
n=-21
| -17=0.5(2x-4) | | 2/5y+3/6=53/6 | | 2(y-5)/2=10+3y/3 | | 0.3(k+4)=7 | | 14w+3=-18 | | 4/3w=24 | | (3-2x)/4=(5x-7.5)/10 | | (2x+8)+48=90 | | 3y-7=8y-10 | | d=45(0)+50 | | -3x-6(3x-1)=-9 | | 5x^2-38x-48=0 | | 50m^2-24=0 | | 4x+x=7.2+5x | | 1/3(k+4)=7 | | 11-4x=21 | | (3x+8)+48=90 | | b÷4+16=48= | | p/5+2=4 | | 3-2x/4=5x-7.5/10 | | 3(h-10)+4(h+19)=13 | | 2x-1/2=4x+2/3 | | X+12y=20 | | 5x+83(x+2)=0 | | 2x-1/2=4x+3/3 | | 5x-2=1x+2 | | 2.9=y/6 | | 2x-6+4x=24 | | 1x+2=2x+1 | | 6x2+15x-99=0 | | .2x+.5=4 | | -1x+6=1x+2 |